Delphinium nanhuashanense (Ranunculaceae), a new plant species from northwestern China - Yang, Bo; Wang, Wenqiang; Tian, Congyan; Wei, Siyu; Shi, Wenjie; Fan, Yuke; Li, Xiaowei (Phytotaxa, 2026)
Delphinium nanhuashanense, a new species of Ranunculaceae discovered in Nanhua Mountain, Ningxia Hui Autonomous Region, northwestern China, is described. Plants are 50–100 cm tall and densely covered with appressed short pubescence throughout. Leaves are 8–13 cm long and 8–13 cm wide; petioles are nearly equal in length to the leaf blades; basal bracts are leaf-like, while the other bracts are lanceolate, 6–15 mm long and 2–6 mm wide, covered with white short tomentum. Sepals are bluish-purple, 1.8–2 cm long and 1.5 cm wide; the spur is slender, 1.5–2.5 cm long and 2 mm wide, straight or slightly decurved downward in the lower part. Carpels are 3; the ovary is densely covered with grayish-white appressed short pubescence. Follicles are short and broad, 1–1.5 cm long. The discovery of this species increases our knowledge of the diversity within the Delphinium genus, and will further our understanding of its evolutionary and ecological relationships.